Lunar Eclipses Illuminate Timing and Climate Impact of Medieval Volcanism - Ludlow, Francis; Yang, Zhen (Routledge, 2023)
Explosive volcanism is a key contributor to climate variability on interannual to centennial timescales1. Understanding the far-field societal impacts of eruption-forced climatic changes requires firm event chronologies and reliable estimates of both the burden and altitude (that is, tropospheric versus stratospheric) of volcanic sulfate aerosol2,3. However, despite progress in ice-core dating, uncertainties remain in these key factors4. This particularly hinders investigation of the role of large, temporally clustered eruptions during the High Medieval Period (HMP, 1100-1300 CE), which have been implicated in the transition from the warm Medieval Climate Anomaly to the Little Ice Age5. Here we shed new light on explosive volcanism during the HMP, drawing on analysis of contemporary reports of total lunar eclipses, from which we derive a time series of stratospheric turbidity. By combining this new record with aerosol model simulations and tree-ring-based climate proxies, we refine the estimated dates of five notable eruptions and associate each with stratospheric aerosol veils. Five further eruptions, including one responsible for high sulfur deposition over Greenland circa 1182 CE, affected only the troposphere and had muted climatic consequences. Our findings offer support for further investigation of the decadal-scale to centennial-scale climate response to volcanic eruptions.
Routledge Handbook of the Digital Environmental Humanities,
Keywords: Digital Humanities; Making Ireland; Smart & Sustainable Planet; Digital Humanities; Humanities; ICE CORE; Lunar eclipse; Medieval Europe; Medieval History; PALEOCLIMATE; Tree-Ring; Volcanology; dendrochronology; environmental history; explosive volcanism; Environment and housing; History